ENVIRONMENTAL RISK FACTORS IN COASTAL AREA OF WAWATU VILLAGE, MORAMO SUB DISTRICT, NORTH OF SOUTH KONAWE, SOUTHEAST SULAWESI - Lestari, Hariati; Bahar, Hartati; Asfian, Pitrah; Ali Imran Ahmad, La Ode (YCAB Publisher & IAKMI SULTRA, 2017)
Aim: This survey study aims to assess and describe environmental risk factors in Wawatu Village, Moramo sub district, North of South Konawe, Southeast Sulawesi.Methods: There 43 respondents selected using convenience sampling. Data were collected using self-questionnaire and observation sheet, consisting of physical condition dimension, chemical and biological factors. Data were analyzed using descriptive statistics. Results: Findings show that 77% of respondents had a good water condition, however, 77% of them had no latrines, 93% had no severage channel, and 63% no landfills. Some of respondents (28%) disposed of ship waste (28%) and household waste (28%) in the sea. Sadly, 81% of respondents did not defecate in the toilet.Conclusions: This study provides the evidence that the health environment in Wawatu Village, Moramo sub district, North of South Konawe, Southeast Sulawesi, needs to more attention. Government and Public health workers need to do great efforts in controlling the risk factors, build the health structure, and implement health promotion program in this area.